Olive oil mill wastewater valorisation by fungi - Crognale, S.; D'Annibale, A.; Federici, F.; Fenice, M.; Quaratino, D.; Petruccioli, M.
This paper presents a brief survey of studies conducted at the Laboratory of Applied and Environmental Microbiology of the University of Tuscia on the possible biotechnological valorisation of olive mill wastewater (OMW)using fungi. Besides being a serious environmental problem, OMW might be a possible resource owing to the presence of added value products (e.g. antioxidants)and of simple and complex sugars as a basis for fermentation processes. To this end the technical feasibility of various fungal fermentative processes either to obtain products of high added value or to improve its agronomic use has been assessed. With regard to the former aspect the following cases of study are described: production of enzymes, such as lipase by Candida cylindracea NRRL Y-17506, laccase and Mn-dependent peroxidase by Panus tigrinus CBS 577.79 and pectinases by Cryptococcus albidus var. albidus IMAT 4735, and exopolysaccharide production by Botryosphaeria rhodina DABAC-P82. As far as agronomic use of the waste is concerned, a process based on the acidogenic fungus Aspergillus niger NB2 and aimed at increasing the phosphorus content of OMW is also reported.
Keywords: OLIVE OIL MILL WASTEWATER; FUNGAL VALORISATION; ENZYMES; EXOPOLYSACCHARIDES; PHOSPHORUS ENRICHMENT; LAND SPREADING